Tafsir Atas Hukum Memerangi Orang Kafir Perspektif Maqāṣid al-Qur’ān Abū Bakr Al-Jaṣṣāṣ - Moqsith, Abd.; Jayadi, Hirman (Ushuluna: Jurnal Ilmu Ushuluddin, 2025)
This article discusses the interpretation of Qur’anic verses that command fighting disbelievers through the maqāṣid al-Qur’ān approach of Abū Bakr al-Rāzī al-Jaṣṣāṣ. The study focuses on verses from Surah al-Tawbah, which are often understood textually and literally without considering their historical context and the overarching objectives of Islamic law. Using a method of ijtihād based on strong presumption (gālib al-ẓann), al-Jaṣṣāṣ emphasizes the importance of understanding the sociopolitical context of these verses, particularly in relation to peace treaties and their violation by the Meccan polytheists. This approach becomes highly relevant in the context of modern nation-states such as Indonesia, which is pluralistic and upholds the principle of citizenship. Through the maqāṣid al-Qur’ān framework—which prioritizes the protection of life, religion, intellect, lineage, and property—this article argues that the call to fight disbelievers in the Qur’an, particularly in Surah al-Tawbah verses 5 and 36, cannot be applied to non-Muslim communities in contemporary Indonesia. Therefore, a contextual interpretation grounded in maqāṣid offers an inclusive and constructive approach to preserving interreligious harmony in the modern era.